Concerns about genetic testing for schizophrenia among young adults at clinical high risk for psychosis. Issue 3 (2nd July 2016) - Lawrence, Ryan E.; Friesen, Phoebe; Brucato, Gary; Girgis, Ragy R.; Dixon, Lisa
ABSTRACT: Background : Genetic tests for schizophrenia may introduce risks and benefits. Among young adults at clinical high risk for psychosis, little is known about their concerns and how they assess potential risks.Methods : We conducted semistructured interviews with 15 young adults at clinical high risk for psychosis to ask about their concerns.Results : Participants expressed concerns about test reliability, data interpretation, stigma, psychological harm, family planning, and privacy. Participants' responses showed some departure from the ethics literature insofar as participants were primarily interested in reporting their results to people to whom they felt emotionally close, and expressed little consideration of biological closeness. Additionally, if tests showed an increased genetic risk for schizophrenia, four clinical high-risk persons felt obligated to tell an employer and another three would "maybe" tell an employer, even in the absence of clinical symptoms.Conclusions : These findings suggest opportunities for clinicians and genetic counselors to intervene with education and support.